THE CORRELATION BETWEEN STUDENTS’ INTEREST IN SPEAKING AND THEIR SPEAKING SCORE - Dj, MUHAMMAD ZUHRI; WAHYUNI, WAHYUNI (DIDAKTIKA, 2017)
This research presents about the correlation between students’ interest in speaking and their speaking score at the sixth semester of STAIN Watampone. This research used quantitative method. The sample consisted of 40 students of the sixth semester of STAIN Watampone. In collecting data, the researcher got the students’ data by using questionnaire. In this research has one problem, “it is How is the correlation between students’ interest in speaking and the level of students’ speaking score”?. The result of the study shown that the result of students interests score is 100. It means that the mean score of students is greater than 30, it is indicate that the effect of students’ interest is positive. Students speaking score is 84.7 It means the level of students speaking score is very high. From the data could be conclude that there is correlation between students’ interest in speaking and the level of students’ speaking score at STAIN Watampone and there is significant. Therefore, H0 was rejected and H1 was accepted.